2011
DOI: 10.1364/ol.36.003930
|View full text |Cite
|
Sign up to set email alerts
|

Subwavelength-size solid immersion lens

Abstract: We report on the fabrication and characterization of nanoscale solid immersion lenses (nano-SILs) with sizes down to a subwavelength range. Submicrometer-scale cylinders fabricated by electron-beam lithography are thermally reflowed to form a spherical shape. Subsequent soft lithography leads to nano-SILs on transparent substrates for optical characterization. The optical characterization is performed using a high-resolution interference microscope with illumination at 642 nm wavelength. The focal spots produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 19 publications
0
25
0
Order By: Relevance
“…Recent experimental work has shown that subwavelength-scale SILs demonstrate a reduced-size focal spot [4]. Further investigation of nano-SILs of different shapes was reported as well [5].…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…Recent experimental work has shown that subwavelength-scale SILs demonstrate a reduced-size focal spot [4]. Further investigation of nano-SILs of different shapes was reported as well [5].…”
Section: Introductionmentioning
confidence: 85%
“…Initially, macroscopicsize SILs were the main subject due to the state of fabrication technologies. Recent advances in micro-and nano-fabrication technologies led to the development of different types of SILs, including diffractive SILs [2], micrometer-size SILs [3] and wavelength-scale SILs [4].…”
Section: Introductionmentioning
confidence: 99%
“…SILs with diameters in the micrometer region [12] down to sub-wavelength size [13] are described in the literature. Brunner et al propose a diffraction-based solid immersion lens (dSIL) as an alternative to the conventional design based on refraction [14].…”
Section: The Near-field Accessed With Solid Immersion Lens Technologymentioning
confidence: 99%
“…millimeter range dimensions, due to the lack of advanced fabrication technologies. The advance of micro-and nano-technology boosts the developments of different types of solid immersion lenses, for instance, diffractive SILs 6 , micro-size SILs 7,8 , nano-size SIL-like elements 9,10 , and subwavelengthsize SILs 11 . The reported micro-size SILs in Refs.…”
Section: Introductionmentioning
confidence: 99%
“…When the SILs are large, the fabrication and alignment errors produce substantial aberrations because the amount of aberrations is proportional to the size of the optical elements. Therefore, when the characteristic size of the SIL becomes smaller and falls within the wavelength size, aberrations, especially the spherical aberration, become negligible 11 . In the visible, the size of a few micrometers is a good target value to avoid aberration effects and at the same time to facilitate the fabrication processes.…”
Section: Introductionmentioning
confidence: 99%